A dual enzyme system composed of a polyester hydrolase and a carboxylesterase enhances the biocatalytic degradation of polyethylene terephthalate films. Issue 8 (21st June 2016) - Barth, Markus; Honak, Annett; Oeser, Thorsten; Wei, Ren; Belisário‐Ferrari, Matheus R.; Then, Johannes; Schmidt, Juliane; Zimmermann, Wolfgang
Abstract: TfCut2 from Thermobifida fusca KW3 and the metagenome‐derived LC‐cutinase are bacterial polyester hydrolases capable of efficiently degrading polyethylene terephthalate (PET) films. Since the enzymatic PET hydrolysis is inhibited by the degradation intermediate mono‐(2‐hydroxyethyl) terephthalate (MHET), a dual enzyme system consisting of a polyester hydrolase and the immobilized carboxylesterase TfCa from Thermobifida fusca KW3 was employed for the hydrolysis of PET films at 60°C. HPLC analysis of the reaction products obtained after 24 h of hydrolysis showed an increased amount of soluble products with a lower proportion of MHET in the presence of the immobilized TfCa. The results indicated a continuous hydrolysis of the inhibitory MHET by the immobilized TfCa and demonstrated its advantage as a second biocatalyst in combination with a polyester hydrolase for an efficient degradation oft PET films. The dual enzyme system with LC‐cutinase produced a 2.4‐fold higher amount of degradation products compared to TfCut2 after a reaction time of 24 h confirming the superior activity of his polyester hydrolase against PET films. Abstract : Biocatalytic degradation of polyethylene terephthalate (PET) by a dual enzyme reaction system. PET was hydrolyzed to mono‐(2‐hydroxyethyl) terephthalate (MHET) with the polyester hydrolases TfCut2 and LC‐cutinase. MHET, an inhibitor of the polyesterases, was simultaneously hydrolyzed by the immobilized carboxylesterase TfCa resulting in a significant enhancement of the enzymatic PET hydrolysis process.